2021
DOI: 10.1038/s41598-021-01439-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of blueberry stunt phytoplasma in Eastern Canada using cpn60-based molecular diagnostic assays

Abstract: Blueberry stunt phytoplasma (BBSP; ‘Candidatus Phytoplasma asteris’) is an insect-vectored plant pathogen that causes severe yield losses in blueberry (Vaccinium corymbosum), which is the most valuable fruit crop in Canada. Rapid, field-based diagnostic assays are desirable tools for the control of BBSP, as part of an integrated, proactive approach to production management termed biovigilance. We designed and validated a chaperonin-60 (cpn60)-targeted LAMP assay for detection of BBSP, providing a rapid, low co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…This could explain why we see how the number of samples for certain hosts is high in some years and then decreases in the following years. That could be the case for BbSP, a disease we know has been present during all the past decade in Quebec (Pérez-López et al 2019;Rosete et al 2019;Hammond et al 2021), but we only see a high number of samples up to 2015, and an increase later in 2020 (Table 1, Fig. 1B).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…This could explain why we see how the number of samples for certain hosts is high in some years and then decreases in the following years. That could be the case for BbSP, a disease we know has been present during all the past decade in Quebec (Pérez-López et al 2019;Rosete et al 2019;Hammond et al 2021), but we only see a high number of samples up to 2015, and an increase later in 2020 (Table 1, Fig. 1B).…”
mentioning
confidence: 67%
“…P. phoenicium’-related strain infecting blueberry plants, which previous studies showed to be typically infected by ‘ Ca . P. asteris’ causing blueberry bushy stunt disease (BbSP) (Pérez-López et al 2019; Arocha-Rosete et al 2019; Hammond et al 2021). However, blueberry plants have been reported infected by ‘ Ca .…”
mentioning
confidence: 99%
“…Few studies have reported leafhoppers in strawberries and raspberries (Linck and Reineke 2019). However, a new study from our group identified a high diversity of leafhoppers in strawberry fields (Plante et al 2023), evidence that the low number of reports might not be linked to host preference but probably to the economic importance of other crops and/or relevant phytoplasma diseases detected affecting those crops, and therefore, demanding primary studies (e.g., blueberry and lingonberry stunt phytoplasma diseases, grapevines yellows disease, and strawberry green petal disease) (Olivier et al 2014, Arocha-Rosete et al 2015, 2019, Pérez-López et al 2019, Hammond et al 2021, Brochu et al 2022, Plante et al 2023). Although many leafhopper species are associated with commercial crops, the number of known vectors is relatively low (Fig.…”
Section: Leafhoppers Phytoplasma and Berries In The Last Decade In Ca...mentioning
confidence: 99%
“…Because of their economic importance in Canada and the United States, blueberries have been one of the main crops studied to survey potential vectors (Pagé 2013), improve phytoplasma detection (Hammond et al 2021), and disentangle associations between viruses and phytoplasmas in the blueberry stunt disease complex (Arocha et al 2019). However, those studies were primarily done in Canada.…”
Section: Leafhoppers Phytoplasma and Berries In The Last Decade In Ca...mentioning
confidence: 99%
See 1 more Smart Citation